Diet containing glycerine and soybean oil can reduce ruminal biohydrogenation in Nellore steers - Granja-Salcedo, Yury Tatiana [UNESP]; de Souza, Vinícius Carneiro [UNESP]; Dias, Ana Veronica Lino [UNESP]; Gomez-Insuasti, Arturo Samuel [UNESP]; Messana, Juliana Duarte [UNESP]; Berchielli, Telma Teresinha [UNESP] (Elsevier, 2017)
This study was conducted to evaluate the effects of the addition of crude glycerine and soybean oil into the diet on the rate of ruminal biohydrogenation (BH), duodenal flow, and on the intestinal digestibility of fatty acids (FA), as well as on the major bacterial species that participate in the BH. Eight castrated Nellore steers were fitted with ruminal and duodenal cannulas. The diet ingredients used were: Tifton 85 hay (roughage source), and a concentrate composed of ground corn, soybean meal and urea, together with 100 g/kg of dry matter (DM) of crude glycerine (CG) or 60 g/kg DM of soybean oil (SO) or 100 g/kg DM crude glycerine plus 60 g/kg (DM) soybean oil (CGSO). Data were analyzed as a double Latin square 4 × 4 design (four treatments and four periods), balanced for residual effects, in a factorial arrangement (A × B). The fixed effect of factor A corresponds to the provision of SO, and that of factor B to the provision of CG. The dry matter intake (DMI) suggested an interaction between CG and SO (P = 0.045); animals fed with the CG diet presented higher dry matter intake (DMI) than those fed the SO and CGSO diets (P < 0.05); however, the CGSO diet led to a DMI similar to that obtained with the CO diet, and higher than that obtained with the SO diet. A higher duodenal flow of monounsaturated FA (MUFA), poly-unsaturated FA (PUFA) and unsaturated FA (UFA) was observed with the CGSO diet (P < 0.05). There was an interaction between CG and SO on the ruminal BH rate of PUFA, UFA, and linolenic acid, the BH being lower with the CGSO diet than with the SO diet (P < 0.05). This interaction was also observed to affect the BH rate of MUFA, which was lower with the CGSO diet than with the SO and CG diets. The SO diet reduced the population of Ruminococcus flavefaciens (P = 0.046), R. albus (P = 0.028) and Fibrobacter succinogenes (P = 0.041). However, the relative proportion of Anaerovibrio lipolytica increased in the diets containing CG (P = 0.043). The association of CG and SO in the diet limited the BH of UFA, and increased the duodenal flow of these acids without influencing the cellulolytic bacteria of the rumen; therefore, this association may be a nutritional strategy to increase the deposition of healthy UFA in meat; however, this needs to be further investigated.
Keywords: Glycerol; Lipolysis; Ruminal bacteria; Unsaturated fatty acids